Die Aktenanalyse als kriminologische Forschungsmethode - Hermann, Dieter (Kriminologische Forschung in den 80er Jahren ; [3,2], 1988)
The research conceming the method of document-analysis is relatively young and fragmentary. Particularly the relation between documents and reality is still unexplored. There are different models to describe the (re-)construction of reality in legal documents: a producer of documents can either benefit from the information contained in already existing documents (Model of Preserving Information) or he can use the dient himself as a source of information (Model of Reality-Orientation). Both models have been examined in this investigation. The data: reports and documents from juvenile bureau officers, judges of Juvenile Courts, probation and parole officers. The results: in general, the Model of Reality-Orientation has proved to be preferable. For information transfer between juvenile bureau officers and judge, however, the Model of Preserving Information is advisable for certain subjects. The reliability of information drawn from official documents depends largely on the technical aspects of information transfer - mainly the quality and quantity of the contact between document-producer and dient. Thus, subjective information drawn from documents can only to a very limited extent be interpreted as an undistorted copy of reality. The thesis of information drawn from documents having their own dynamics, which are supposed to be leading to a progressively negative valuation of the dient, can be rejected.